Social Determinants of Health in the Digital Age: Determining the Source Code for Nurture. - Abnousi, Freddy; Rumsfeld, John S.; Krumholz, Harlan M. (JAMA: Journal of the American Medical Association, 2019)
In this Viewpoint, Harlan Krumholz and colleagues discuss the promise that social media data hold for helping researchers better understand social determinants of health, and the challenges that must be overcome to reliably link social network data to clinical and health outcomes.